Pengaruh Media Irene’s Donut terhadap Peningkatan Pengetahuan dan Perilaku Ibu dalam Mencegah Karies Gigi pada Anak Prasekolah - Widodo, Yufen; Ismalayani, Ismalayani (Jurnal Kesehatan, 2022)
Caries are a common dental health problem in children. There are four causes of caries, namely host (host), agent (microflora), environment (substrate), and time. Individual counseling methods such as Irene's Donut method can lead parents to educate their children in maintaining dental health habits from an early age. This method aims to make parents aware of the risk factors for caries and provide a menu on how to deal with caries disease, in hope that it can empower the community to be independent. Dental health behavior includes knowledge, attitudes, and actions related to the concept of healthy and the prevention efforts for toothache. This type of research uses a quasi-experimental with a one-group pre-test post-test research design. The population and sample in this study were kindergarten students in the District of Ilir Barat I Palembang City. The number of samples was 68 pairs of students and mothers with a total of 136 with the random sampling technique. The data obtained were tested using the T-test analysis, used when the data is normally distributed. The results showed that there were differences in maternal knowledge and behavior before and after counseling with Irene's Donuts media. Irene's Donuts media is effective in increasing the knowledge and behavior of mothers in preventing dental caries in children in Kindergarten, Ilir Barat I District, Palembang City.